2019
DOI: 10.3389/fgene.2019.00058
|View full text |Cite
|
Sign up to set email alerts
|

The Role of AKT3 Copy Number Changes in Brain Abnormalities and Neurodevelopmental Disorders: Four New Cases and Literature Review

Abstract: Microdeletions at 1q43-q44 have been described as resulting in a clinically recognizable phenotype of intellectual disability (ID), facial dysmorphisms and microcephaly (MIC). In contrast, the reciprocal microduplications of 1q43-q44 region have been less frequently reported and patients showed a variable phenotype, including macrocephaly. Reports of a large number of patients with copy number variations involving this region highlighted the AKT3 gene as a likely key player in head size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…However, number of genes located on chromosome 1q, such as AKT3, PIK3C2B, MDM4 and NOTCH2NL, are known to be associated with the control of cell proliferation, survival, migration, stress response, oncogenic transformation, neuronal differentiation and intracellular protein trafficking. [54][55][56][57] Interestingly, these genes were found to be overexpressed in ZFN-NSCs with dup(1)q and inhibitor studies suggested that AKT3 pathway may be at least partially responsible for their increased proliferation rate. In conclusion, we show that an isolated duplication of chromosome 1q occurs in unmodified and ZFN-modified hiPSC-NSCs after prolonged passaging, that this aberration increases NSC proliferation rate in vitro, and that these changes still persist in transplanted cells in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, number of genes located on chromosome 1q, such as AKT3, PIK3C2B, MDM4 and NOTCH2NL, are known to be associated with the control of cell proliferation, survival, migration, stress response, oncogenic transformation, neuronal differentiation and intracellular protein trafficking. [54][55][56][57] Interestingly, these genes were found to be overexpressed in ZFN-NSCs with dup(1)q and inhibitor studies suggested that AKT3 pathway may be at least partially responsible for their increased proliferation rate. In conclusion, we show that an isolated duplication of chromosome 1q occurs in unmodified and ZFN-modified hiPSC-NSCs after prolonged passaging, that this aberration increases NSC proliferation rate in vitro, and that these changes still persist in transplanted cells in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of specific driver gene(s) on chromosome 1q responsible for this effect in NSCs or cancer cells is difficult because more than one gene could be involved in conveying the growth advantage to aneuploid cells. However, number of genes located on chromosome 1q, such as AKT3 , PIK3C2B , MDM4 and NOTCH2NL, are known to be associated with the control of cell proliferation, survival, migration, stress response, oncogenic transformation, neuronal differentiation and intracellular protein trafficking 54‐57 . Interestingly, these genes were found to be overexpressed in ZFN‐NSCs with dup(1)q and inhibitor studies suggested that AKT3 pathway may be at least partially responsible for their increased proliferation rate.…”
Section: Discussionmentioning
confidence: 99%
“…GSK-3β is a negative regulator of cyclin D1 and D2 by ubiquitin dependent degradation. The AKT family of proteins are implicated in a wide range of human diseases including cancer, diabetes, cardiovascular and neurological disease (Alcantara et al, 2017;Chung et al, 2014;Conti et al, 2015;Dobyns & Mirzaa, 2019;Gai et al, 2015;Grabinski et al, 2011;Hers et al, 2011;Lee et al, 2012;Lopes et al, 2019;Mure et al, 2010;Poduri et al, 2012;Riviere et al, 2012;D. Wang et al, 2013;Yang et al, 2005).…”
Section: Akt3mentioning
confidence: 99%
“…Akt3 knockout mice display microcephaly suggesting that it plays a critical role in determining brain size (Easton et al, 2005;Yang et al, 2005). Mosaic and constitutional gain-of-function variants of AKT3 are associated with MPPH syndrome (Lee et al, 2012;Lopes et al, 2019;Poduri et al, 2012;Riviere et al, 2012), with more than 20 patients reported to date with molecularly confirmed AKT3 related megalencephaly (Alcantara et al, 2017;Harada et al, 2015;Jamuar et al, 2014;Nakamura et al, 2014;Negishi et al, 2017;Nellist et al, 2015;Riviere et al, 2012). A subset of affected individuals is mosaic for the common p.E17K mutation causing hemimegalencephaly (Jansen et al, 2015;Lee et al, 2012;Poduri et al, 2012;Riviere et al, 2012).…”
Section: Akt3mentioning
confidence: 99%
“…They comprise candidate ID-causative loci located in 1q43-q44, 2q11.2-q12.2, 7q33, 10q26.3, 17p11.2 and 20q13.12-q13.13 (losses); 1p22.1-p21.3, 7q33, 9q33.2-q33.3, 9q34.3, Xq24 and Xq26.3 (gains) (Table 2). Patients with 1q43-q44, 7q33 and 10q26.3 CNVs have been described elsewhere in detail [5–7]; the patient with a 9q34.3 gain is described together with patient R14 in Part 1 of Additional file 1; therefore, we focus next on the remaining candidate loci .…”
Section: Resultsmentioning
confidence: 99%